The Role and Function of the Sharia Supervisory Board in Supervising Sharia Banking (Study at BPRS Maslahat Dana Syariah Nusantara) - Dafta Zatiwa; Desi Isnaini; Herlina Yustati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine the role and function of the Sharia Supervisory Board in supervising BPRS Maslahat Dana Syariah Nusantara, the supervisory mechanism implemented by the Sharia Supervisory Board towards BPRS Maslahat Dana Syariah Nusantara, and the obstacles faced by the Sharia Supervisory Board in carrying out its supervisory function at BPRS Maslahat Dana Syariah Nusantara. This study uses a qualitative descriptive approach with field methods at PT BPRS Maslahat Dana Syariah Nusantara, Bengkulu. Data were collected through interviews, observations, and documentation, with informants selected using purposive sampling. Data analysis was carried out through collection, reduction, presentation, and drawing conclusions. The results of the study indicate that 1) the Sharia Supervisory Board of BPRS Maslahat Dana Syariah Nusantara Bengkulu plays a role in ensuring sharia compliance, reviewing and approving new products/services, conducting routine supervision and sharia audits, and submitting DSN-MUI fatwas to BPRS practices, 2) The supervisory mechanism of the Sharia Supervisory Board at BPRS Maslahat Dana Syariah Nusantara Bengkulu includes the appointment of members, supervision of bank operations, reporting of supervision results, and implementation of regulations to support sharia principles, and 3) Constraints of the Sharia Supervisory Board at BPRS Maslahat Dana Syariah Nusantara include limited competence and human resources, high workload and dual positions, as well as regulations and governance that do not fully support optimal sharia supervision.